2016
DOI: 10.1002/pro.3017
|View full text |Cite
|
Sign up to set email alerts
|

From membrane tension to channel gating: A principal energy transfer mechanism for mechanosensitive channels

Abstract: Mechanosensitive (MS) channels are evolutionarily conserved membrane proteins that play essential roles in multiple cellular processes, including sensing mechanical forces and regulating osmotic pressure. Bacterial MscL and MscS are two prototypes of MS channels. Numerous structural studies, in combination with biochemical and cellular data, provide valuable insights into the mechanism of energy transfer from membrane tension to gating of the channel. We discuss these data in a unified two-state model of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…Sugar transport is usually very efficient and might increase the internal pressure to a deleterious level. Also, a variety of metabolites and ions may suddenly be absent in the environment, placing the cell in low osmolarity: this would result in membrane disruption, unless specific safety valves, the mechanosensitive channels where opening pores in the membrane is reminiscent of the iris diaphragm movement (Zhang et al ., ).…”
Section: Any Important Need Elicits An Adaptive Functionsupporting
confidence: 55%
“…Sugar transport is usually very efficient and might increase the internal pressure to a deleterious level. Also, a variety of metabolites and ions may suddenly be absent in the environment, placing the cell in low osmolarity: this would result in membrane disruption, unless specific safety valves, the mechanosensitive channels where opening pores in the membrane is reminiscent of the iris diaphragm movement (Zhang et al ., ).…”
Section: Any Important Need Elicits An Adaptive Functionsupporting
confidence: 55%
“…Those authors found that SpoVAC-myc-His 6 protected E. coli to a similar extent as MscL, a well-studied mechanosensing membrane protein (45, 46). The authors further characterized the protein in conductance studies and found that, when recombinant-expressed in E. coli and embedded in lipid vesicles, SpoVAC had a pore size of 4.6 Å (13).…”
Section: Discussionmentioning
confidence: 95%
“…These pressure changes stretch the membrane to alter the lateral pressure profile, the complex profile of forces that vary with location across the bilayer (11)(12)(13). MS channels embedded within the bilayer have been shown to directly respond to these changes (14,15). The application of either positive or negative pressure increases the overall tension within both leaflets of the bilayer, and there is now a large body of evidence demonstrating how such changes in lateral tension underlie the activation of MS channels (2)(3)(4)(5).…”
mentioning
confidence: 99%